2004
DOI: 10.1007/s00024-003-2429-6
|View full text |Cite
|
Sign up to set email alerts
|

2-D Crustal Velocity Structure Along Hirapur-Mandla Profile in Central India: An Update

Abstract: The 2-D crustal velocity model along the Hirapur-Mandla DSS profile across the Narmada-Son lineament in central India (MURTY et al., 1998) has been updated based on the analysis of some short and discontinuous seismic wide-angle reflection phases. Three layers, with seismic velocities of 6.5-6.7, 6.35-6.40 and 6.8 km s )1 , and upper boundaries located approximately at 8, 17 and 22 km depth respectively, have been identified between the basement (velocity 5.9 km s )1 ) and the uppermost mantle (velocity 7.8 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 9 publications
2
31
1
Order By: Relevance
“…It is also seen in the model that the granite layer is missing in the right margin of the faulted basin whereas it has a thin patch in its left side of the faulted segment. This conforms to the reported DSS modeling (MURTY et al, 2004).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is also seen in the model that the granite layer is missing in the right margin of the faulted basin whereas it has a thin patch in its left side of the faulted segment. This conforms to the reported DSS modeling (MURTY et al, 2004).…”
Section: Resultssupporting
confidence: 92%
“…Using constraints from the borehole data (DAS et al, 1999) and DSS studies (MURTY et al, 2004) Vol. 164, 2007 Optimum Design of Survey Network 2019 scaling spectral analysis (MAUS and DIMRI, 1994, 1995a,b, 1996 of the data.…”
Section: Resultsmentioning
confidence: 99%
“…2414 A. S. N. Murty et al Pure appl. geophys., correlatable crustal P-wave phases P 3 P to P M P (MURTY et al, 2004), in the record section of SP 235, the presence of prominent reflection phases P 6 P-P 9 P (Fig. 2a).…”
Section: Data Analysis and Interpretationmentioning
confidence: 97%
“…Observed record section (normalized) of SP 235 recorded towards SP 0 (distances are from SP 0) along the profile assembled from the digitized data of DSS records (trace interval 800 m). Theoretical travel-time curves, corresponding to the velocity-depth model of MURTY et al (2004) are shown as (P 3 P to P M P) for various phases correlated in the record section. P 6 P, P 7 P, P 8 P and P 9 P are the subcrustal reflection phases identified and modeled in the present study.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation